Students' Tabayyun Practice in Using Artificial Intelligence: A Study of The Living Qur'an Qs. Al-Hujurat [49]:6 - Nisa, Karimatan (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This study aims to analyze how the value of tabayyun in QS. al-Hujurāt [49]:6 can be actualized as an ethical framework for the use of Artificial Intelligence (AI) by students in an academic context. Methodology: This study employed a qualitative, library-based research approach. Data were obtained from tafsir books, scientific journals, and previous research relevant to the use of Artificial Intelligence by students. The analysis was conducted using a Living Qur'an approach, examining how the value of tabayyun (reconciliation) in Surah al-Hujurāt [49]:6 is reflected in the phenomenon of AI use among students, based on literature data. Results: The findings indicate that the principle of tabayyun (reconciliation) has profound relevance as an ethical foundation for the use of AI, particularly in fostering critical thinking, information verification, and intellectual responsibility. However, in contemporary academic practice, this value is often neglected due to technological dependence, and a lack of values-based digital literacy. AI, while beneficial, has the potential to erode cognitive autonomy and exacerbate disinformation if not governed by moral principles such as tabayyun (reconciliation). Applications/Originality/Value: This research provides an original contribution through a contextual reinterpretation of QS. al-Hujurāt [49]:6 within the discourse of AI ethics. The findings not only enrich the Living Qur'an paradigm in the digital era but also offer a theoretical basis for the development of ethical guidelines, an Islamic-values-based digital literacy curriculum, and academic policies responsive to the challenges of generative technology in higher education.